PENGARUH PENGHINDARAN PAJAK DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Christian Ignatius; Indra Arifin Djashan (E-Jurnal Akuntansi TSM, 2021)
This research has a purpose to obtain empirical evidence about the influences of Tax Avoidance, Return on Asset, Current Ratio, Debt to Equity Ratio, Total Asset Turn Over, Sales Growth, Free Cash Flow, Company Size as independent variables on the Firm Value as a dependent variable. The population in the research is manufacturing companies that listed in the Indonesia Stock Exchamge (IDX) at period 2018 until 2020. The sample used for this research consist of 59 listed manufacturing companies that listed in Indonesia Stock Exchange (IDX). The selection of these sample used the purposive sampling method with total 177 research data and the data analysis method in the research is used multiple regression analysis. The result in this research indicated that Return on Asset and Debt to Equity Ratio have positive influence on Firm Value.